A study of oxide/CdTe interfaces for CdTe photovoltaics using atomistic modeling - Thiyagarajan, Aanand, author; Sampath, W. S., advisor; Weinberger, Christopher, advisor; Martinez Pozzoni, Umberto, committee member; Sites, James R., committee member; Popat, Ketul, committee member (Colorado State University. Libraries, 2021)
Solar photovoltaics (PV) has undergone a dramatic transformation over the past few decades and is now a widespread electricity generation source. Among currently existing PV technologies, the thin film sector led by cadmium telluride is the most promising. Cadmium Telluride (CdTe) PV has experienced unprecedented growth and is now a major commercial player. However, the field has a few challenges to overcome until it reaches its full potential. The focus of this study is the interface between the CdTe-based absorber and the front window layer. Traditionally, cadmium sulfide has been used as the window layer in such devices. At the Next Generation Photovoltaics (NGPV) center in Colorado State University, superior devices have been demonstrated using magnesium zinc oxide (MgxZn1-xO or MZO) as the window layer. This is attributed to the larger bandgap of MZO causing a pickup in the current and the open circuit voltage. A magnesium to zinc atomic ratio of 23:77 has shown optimal performance characteristics. Alloying CdTe with Se to form cadmium selenium telluride (CdSexTe1-x or CST) has resulted in further improvements. One way to determine the quality of an interface is to study the electronic band alignment at that interface. Existing band alignment models show only limited features and hence there is a need for a more sophisticated approach to investigate complex characteristics. This study uses atomistic modeling based on Density Functional Theory (DFT) to investigate certain structural and electronic properties of the oxide and the oxide/absorber interface. The technique solves for electronic structures of materials based on electron density and predicts the structural properties of materials to a high degree of accuracy. Electronic characteristics are determined using a semi-empirical method known as DFT-1/2. A mathematical formulation called Green's Function (GF) has been incorporated within the model to simulate device structures. The bulk properties of MZO such as lattice constant, band gap, band edges and electron effective mass are established and compared to experiment. Following this, the band alignment at the MZO/CdTe and MZO/CST interfaces is determined, along with band offsets and interface states. The influence of chlorine in the deposition process is also investigated. This work is the first of its kind to study the oxide-CdTe and oxide/CST interfaces using DFT+GF and provides new insights into the electronic characteristics at the interface. Bulk properties of the MZO match experimental reports. Termination chemistry plays a significant role in the band bending and in the presence of defect states at the oxide/absorber interface. Calculations indicate that a Mg/Zn-Te interface is energetically preferred, with experimental reports pointing to the same. Moreover, varying the magnesium composition in the MZO alloy affects the magnitude of the band offsets. The interface band alignment results are close to those seen experimentally. A small amount of chlorine may help alleviate interface defect states by chemical passivation, possibly due to the removal of dangling bonds.
Keywords: photovoltaics; electricity; thin film sector; cadmium telluride; CdTe; CdTe-based absorber; window layer; magnesium zinc oxide; electronic band alignment